An application of pressure/temperature-controlled microwave heating curves for the mineralization of tuna material prior to spectrometric quantification of mercury - Tahán, Jorge; Sanchéz, José; Rodríguez, Minerva; Cubillán, Hernán; Granadillo, Víctor; Romero, Romer (Ciencia)
This work presents an application of pressure/temperature-controlled microwave heating curves for monitoring the mineralization the Standard Reference Material of Albacore Tuna RM 50 for the subsequent flow injection cold vapor atomic absorption spectrometric (FI-CVAAS) determination of total mercury (Hg). Mineralizations were performed using a CEM Model MDS-2100 laboratory microwave oven (950 W for 100% power) provided with pressure sensing tube and fiberoptic temperature probe to monitor and control pressure and temperature conditions inside the lined digestion vessels. A Perkin-Elmer Model 5100 PC atomic absorption spectrometer equipped with an electrodeless discharge lamp for Hg, was used in the flow injection mode. A Perkin-Elmer Model FIAS-400 system with an AS-90 autosampler were connected to the spectrometer. Initially, approximately 500 mg of standard test portion were digested with 15 mL of concentrated nitric acid. The mineralization time was 4 min. For nitric acid mineralization, one control vessel, two sample vessels and one blank vessel were employed for simultaneous digestion. After 2.5 min of mineralization time, pressure was kept at approximately 190 psi and temperature decreased down to 150°C. Unfortunately. not more than 20% of the total Hg was recovered. The mineralization of 300 mg of lyophilized test portion with 15 mL of concentrated nitric acid followed. These conditions favored the FI-CVAAS evaluation of total Hg (ca. more than 80% was recovered). The best results were obtained using less sample weight and fewer microwave digestion vessels under the following conditions: addition of 15 mL of concentrated nitric acid to 200 mg of test portion weight, using three digestion vessels (one control vessel. one sample vessel and one blank vessel) irradiated for 4 min. Under these conditions, the FI-CVAAS Hg concentration (0.87 Ó 0.03 Âµg/g) correlated statistically with the certified value (0.95 Ó 0.10 Âµg/g) reported for the reference material Albacore Tuna. The amount of Hg required to give 1% absorption was 314 pg. The detection limit, defined as twice the standard deviation of the blanks. was 164 ng/L which corresponds to 82 pg of Hg for 500 .ÂµL of solution undergoing analysis. Precision (R.S.D.) was better than 3%. In conclusion, monitoring and controlling pressure and temperature inside the digestion vessels guaranteed a much safer mineralization, avoiding chances for explosion of the reactor system and potential injuries to the analyst. In general, pressure/temperature controlled microwave mineralization seems to be reliable alternative for sample descomposition.